Meta-Analysis of the Influence of Cooperative Learning Models on Aspects of Learners' Physical Knowledge - Rif'il Husniyah; Asrizal Asrizal; Fatni Mufit (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2022)
21st-century learning integrates knowledge, attitudes, and skills with mastery of technology. One solution for the learning demands of the 21st century is to apply a cooperative learning model, especially in physics subjects. Researchers used the methodization method in this study with 20 national article sources. The analysis results are reviewed based on the types of cooperative models, grade levels and physics materials contained in the article. Based on the average effect size, the influence of collaborative learning on aspects of students' physical knowledge was obtained in terms of the three groupings in the high category. It states that cooperative learning models have a very effective influence on physics lessons.